Phaeochromocytoma and acute cardiovascular death (with special reference to myocardial infarction). Issue 700 (February 1984) - Cohen, C. D.; Dent, D. M.
Abstract : The causes of death, as determined by autopsy, in 10 patients dying from the acute effects of phaeochromocytoma were myocardial infarction (five patients), left ventricular failure (two patients), cerebral haemorrhage (two patients) and circulatory collapse with malignant phaeochromocytoma (one patient). Most patients died shortly after admission during the course of a fulminant cardiovascular illness and the underlying tumour was unsuspected in eight instances. The clinical features and post-mortem cardiovascular findings are reviewed.